A review of the genus Orionis Shaw (Hymenoptera: Braconidae: Euphorinae) and first records of the genus from South America and the Oriental Region - Bortoni, Marco Aurélio; Shimbori, Eduardo Mitio; Shaw, Scott Richard; Souza-Gessner, Carolina Da Silva; Penteado-Dias, Angélica Maria (Zootaxa, 2016)
Orionis is a small Neotropical euphorine genus, currently in the tribe Perilitini. Although the biology of the genus is unknown, Orionis eximius (Muesebeck) was described from a single female specimen reared from a cocoon associated with Lantana camara. Here, we present a taxonomic revision of Orionis and the first records of the genus from South America and Thailand, with descriptions of three new species: O. brasiliensis sp. nov., O. ecuadoriensis sp. nov. and O. orientalis sp. nov. We also report the first record of O. eximius from South America (Ecuador). A revised key for the described species is presented.